A Harmonic Analysis Method Based on Harris Window for Digital Substation - Luo Hanwu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Accurate and efficient harmonics detection is an important premise and basis for controlling the harmonics. The sampling frequency of the grid voltage and current in digital substation normally must be kept constantly as required by the standard of IEC61850, thus the asynchronous sampling caused by the fluctuating grid frequency and this constant sampling frequency will result in spectral leakage and aliasing which would affect the accuracy of harmonic analysis. In this paper, a double-spectrum-line interpolation Fast Fourier Transform approach based on multi-term Harris window for grid frequency and harmonic measurement was proposed, and the simple and practical adjustment formulas for the frequency, amplitude and phase angle were derived by curve fitting. The correctness and effectiveness of the proposed method were validated by simulation and field test.